2005
DOI: 10.1176/appi.ajp.162.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Personality Dimensions in First-Episode Psychoses

Abstract: The observed association between avoidant personality and schizophrenia supports the recent literature on the comorbidity of nonspectrum personality disorders in schizophrenia. This association may be related to shared neurodevelopmentally mediated impairments in social cognition in schizophrenia and some cluster C personality dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
2
22
0
2
Order By: Relevance
“…Although Craig et al (33) reported that alcoholics had higher MCMI scores than opiate addicts on Schizotypal and Paranoid personality subscales, three reports did suggest a distinct subgroup of opiate addicts with schizoid/ schizotypal pathology. These patients had more legal problems (34), and required a higher methadone dose (35) than opiate addicts with less Cluster A pathology.…”
Section: Discussionmentioning
confidence: 92%
“…Although Craig et al (33) reported that alcoholics had higher MCMI scores than opiate addicts on Schizotypal and Paranoid personality subscales, three reports did suggest a distinct subgroup of opiate addicts with schizoid/ schizotypal pathology. These patients had more legal problems (34), and required a higher methadone dose (35) than opiate addicts with less Cluster A pathology.…”
Section: Discussionmentioning
confidence: 92%
“…For example, Solano and De Chávez (2000) found that 85% of their sample of patients with schizophrenia had premorbid personality disorders, with avoidant (32.5%), schizoid (27.5%), paranoid (20%), dependent (20%), and schizotypal (12.5%) were the most common; they noted, however, that the generalizability of their findings may be limited by their relatively small (N¼ 40) sample. Likewise, Keshavan et al, 2005 found that "Cluster C" dimensional scores on a semi-structured personality interview schedule, particularly avoidant personality scores, were higher for patients with schizophrenia than for patients with non-schizophrenia psychoses or healthy participants. Such findings have been extended to individuals deemed to be at risk for schizophrenia, as Fogelson et al (2007) have demonstrated that a relations exists between avoidant personality disorder and liability to schizophrenia even after statistically accounting for paranoid and schizotypal personality disorders, a finding that was supported by Gooding et al (2007).…”
Section: Introductionmentioning
confidence: 95%
“…However, one study that examined this question directly found social anxiety to be unrelated to clinical psychotic symptoms (Pallanti et al, 2004). More recently, studies have shown that avoidant personality scores were highly intercorrelated with all DSM cluster A personality disorder (Spitzer et al, 1990) dimensional scores and that avoidant personality disorder is highly prevalent in outpatients with schizotypal personality disorder (Keshavan et al, 2005;Battaglia et al, 1995). These latter studies are at odds with the finding that social anxiety symptoms are unrelated to other dimensions of psychosis (Pallanti et al, 2004).…”
Section: Social Anxiety In Schizophrenia Patientsmentioning
confidence: 99%
“…Deciphering the relationship between avoidant personality disorder and other schizophrenia-spectrum disorders requires blind evaluation of relatives of patients with Sz compared to community control relatives. (Keshavan et al, 2005) To address these concerns we examined if avoidant personality disorder shows heightened rates among first degree relatives of Sz probands compared to relatives of control groups and shows heightened rates even when controlling for the presence of schizotypal and paranoid personality disorders. We also examined whether some individual avoidant personality disorder symptoms are more characteristic of relatives of schizophrenics compared to relatives of community controls and if avoidant personality disorder when present in the first degree relatives of Sz probands mainly reflects a near miss for a diagnosis of another schizophrenia-spectrum personality disorder.…”
Section: Social Anxiety Is a Separable Dimension Of Psychopathologymentioning
confidence: 99%